Effectiveness of an Enhanced Nursing Intervention Program Combining Infection Control and Respiratory Function Training in Patients With Leukemia and Respiratory Infections During Chemotherapy - Lu, Yuzhen; Wen, Lianying (Nursing & health sciences, 2025)
ABSTRACT To evaluate the effectiveness of a comprehensive nursing intervention program combining enhanced infection control measures with structured respiratory function training for patients with leukemia and respiratory infections during chemotherapy. 400 adult patients with leukemia in our hospital from May 2023 to June 2024 were randomly assigned to an intervention group or a control group. The intervention group received an enhanced nursing care program, while the control group received standard care. Evaluated outcomes included respiratory function parameters, infection control indicators, quality of life, and patient satisfaction, etc. The intervention group showed significant improvements in respiratory function parameters compared to the control group. Healthcare‐associated infection rates were significantly lower in the intervention group. The intervention group demonstrated shorter hospital stays, reduced antibiotic duration, and lower inflammatory marker levels. Quality of life scores showed greater improvements in the intervention group. Protocol adherence was high (> 90%) across all centers. Comprehensive nursing intervention combining enhanced infection control measures with structured respiratory function training effectively improves clinical outcomes, reduces complications, and enhances quality of life in patients with leukemia and respiratory infections during chemotherapy.